The Effect of Human Resources Management (HRM) Practices on Organizational Commitment of The Class IIA Cikarang Prison Employees - Novita Nur Marlesa; Kusmiyanti Kusmiyanti (Dinasti Publisher, 2025)
Indonesia's human resources are abundant with its large population being one of the largest nations in the world. This shows that there are great opportunities for public organizations. This research was conducted to determine the influence of human resource management (HRM) practices on the organizational commitment of employees at the Class IIA Cikarang Correctional Institution. This is intended because there is a need to manage employees as one of the human resources (HR) in prisons whose numbers do not yet meet needs. As mandated in Permenkumham Number 11 of 2022, correctional institutions need to achieve the title of corruption-free area (WBK) and service-free bureaucratic area (WBBM) as a form of organizational commitment to providing services to inmates and the community. This research uses quantitative methods and data by distributing surveys to 103 employees as a questionnaire. The questionnaire was then measured using SmartPLS and analyzed using structural equation modeling (SEM) with simple regression. The research results show that human resource management practices have a positive and significant influence on the organizational commitment of employees at the Class IIA Cikarang Prison. This research shows that leaders can manage existing employees based on the principle of